Does price competition damage healthcare quality? - Anne-Fleur Roos; Eddy van Doorslaer; Owen O'Donnell; Erik Schutt; Marco Varkevisser (Tinbergen Institute, 2018)
One of the reasons why regulators are hesitant about permitting price competition in healthcare markets is that it may damage quality when information is poor. Evidence on whether this fear is well-founded is scarce. We provide evidence using a reform that permitted Dutch health insurers and hospitals to freely negotiate prices for elective procedures. Unlike previous research that has relied on indicators of the quality of urgent treatments, we take advantage of the plausible absence of selection bias in our setting to identify the effect on quality of non-acute hip replacements. Using administrative data on all admissions to Dutch hospitals, we find no evidence that increased exposure to price competition reduces quality measured by readmission rates, despite the lack of publicly available information on this outcome. In fact, there is evidence of a temporary, positive impact on quality. Our estimated null effect over the full post-liberalization period is robust.
Keywords: I11; L14; L15; 330; Healthcare; hospital; competition; quality; contracting